1996
DOI: 10.1111/j.1600-0447.1996.tb09835.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in schizophrenia: relationship to sociodemographic factors, symptomatology and tardive dyskinesia

Abstract: The influence of sociodemographic, clinical and treatment factors on the quality of life of patients with schizophrenia has yet to be fully defined. We evaluated the quality of life of patients with schizophrenia who were attending a catchment area rehabilitation centre, in order to establish its clinical correlates. These patients had a poor to moderate quality of life which was inversely related to negative symptom severity, illness duration, the cumulative length of previous hospitalization and patient age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
163
11
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(206 citation statements)
references
References 35 publications
(12 reference statements)
22
163
11
10
Order By: Relevance
“…These results confirm that degradation of a person with schizophrenia throughout the course of the disorder leads to a worse quality of life. A study that also used QLS found similar results that a longer duration of the disorder and an older age would be associated with a worse quality of life (21) . In this sense, another study showed that a longer duration of the disorder was a predictor for worse quality of life, despite age not being significantly related to quality of life (15) .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These results confirm that degradation of a person with schizophrenia throughout the course of the disorder leads to a worse quality of life. A study that also used QLS found similar results that a longer duration of the disorder and an older age would be associated with a worse quality of life (21) . In this sense, another study showed that a longer duration of the disorder was a predictor for worse quality of life, despite age not being significantly related to quality of life (15) .…”
Section: Discussionsupporting
confidence: 54%
“…Thus, developing psychoeducation programs for family members is fundamental (18)(19)(20) . People with schizophrenia who lived in institutions had worse quality of life than those who lived alone or with family members (21) . A study in which the participants lived in their own home demonstrated better access to opportunities and resources to improve their quality of life than those living in institutions (22) .…”
Section: Discussionmentioning
confidence: 99%
“…As the studies used the QLS which was originally designed to assess deficit symptoms of schizophrenia, it may stand to reason that fewer negative symptoms were associated with better QOL assessed by the QLS. However, some studies showed the significant associations of positive symptom and other clinical factors with the QLS (17)(18)(19)(20).…”
Section: Relation Between Clinical Symp-toms and Quality Of Lifementioning
confidence: 99%
“…Uma explicação alternativa para a ausência de uma melhor qualidade de vida subjetiva nas mulheres esquizofrênicas em comparação com os homens esquizofrênicos foi proposta por Browne et al 36 Segundo esses autores, o uso de amostras com mulheres com quadros mais graves em estudos de qualidade de vida tenderia a tornar esse grupo mais parecido com o de homens, minimizando a magnitude da associação entre qualidade de vida e sexo.…”
unclassified